(untitled) (Journal of Information Technologies in Education (ITE), 2009)
In articles conceptual methodological approaches in vocational training the future experts in the field of information safety are considered. The author opens essence person-focused, ontologic, akmeologic, sinergosologic and technological approaches in preparation of such experts.